THE ROLE OF STUDENT WORK LECTURE GROUP 52 AS A MANAGEMENT OF SERVICE TO THE COMMUNITY IN THE MIDDLE OF THE COVID-19 PANDEMIC IN MEKARSARI VILLAGE, CARENANG DISTRICT, SERANG REGENCY - Fatari Fatari; Devi Irwan; Dewi Inggrita; Nurfauzi Bagus Haryadi; Fitri Nur Rahman; Jumaroh Jumaroh; Navita Yuliana (International Journal of Engagement and Empowerment, 2021)
The Student Work Lecture (KKM) in 2021 held by Bina Bangsa University is different from previous years. This year it was carried out during the Covid-19 Pandemic directly to the field in groups, not online. With the KKM during the Covid-19 pandemic, this is hope that the students will still have the values of service to develop student competencies and social interactions in the community. This study aims to determine the role of Student Work Lectures as a form of community service. The population and sample in this study were 52 KKM Bina Bangsa University with a total of 20 people from 1314 people in 2021. Data collection methods. They are using interviews, observation and documentation. The interview method in this study is to get information to the public about the beneficial values of KKM activities during the Covid-19 Pandemic in Mekarsari village, Carenang sub-district. The results in this study indicate that the community can still feel KKM activities as a form of community service during the Covid-19 pandemic. The role of students can still be carried out with a series of innovative activities and continue to carry out health protocols.